2012
DOI: 10.17221/5954-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

The branching of the aortic arch in the Eurasian bittern (Botaurus stellaris, Linnaeus 1758)

Abstract: This study was aimed at determining the vascular architecture of the aortic arch in the Eurasian bittern. For this purpose, the heart arteries of two bitterns were evaluated. The latex injection method was used to observe the branching of the aortic arch. Two brachiocephalic trunks were arising separately from the aortic arch and these arteries were giving to the common carotid and subclavian arteries. One of the thin branches arising from the subclavian artery was the sternoclavicular artery, which was in tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
1
4
0
1
Order By: Relevance
“…Similarly, it was reported that the arteria axillaris was a branch of the arteria subclavia on the left side of the body in the long-legged buzzard (Erdogan ve Kilinc, 2014). Likewise, it was stated that the arteria axillaris was a branch ramifying independently from the arteria subclavia in Eurasian bittern (Erdogan, 2012) and it was always a separate vessel in the Whooping Crane (Fisher, 1955). In accordance with these reports, examined in this study, the arteria axillaris was also ramifying from the arteria subclavia as sepa- rate vessel in the sparrowhawk ( Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, it was reported that the arteria axillaris was a branch of the arteria subclavia on the left side of the body in the long-legged buzzard (Erdogan ve Kilinc, 2014). Likewise, it was stated that the arteria axillaris was a branch ramifying independently from the arteria subclavia in Eurasian bittern (Erdogan, 2012) and it was always a separate vessel in the Whooping Crane (Fisher, 1955). In accordance with these reports, examined in this study, the arteria axillaris was also ramifying from the arteria subclavia as sepa- rate vessel in the sparrowhawk ( Fig.…”
Section: Discussionsupporting
confidence: 88%
“…The term ‘aortic vessels' in our paper corresponds to the aortic arch and the brachiocephalic trunk. By contrast to mammals, two brachiocephalic trunks arise from the arch of the aorta and give rise to the common carotid and subclavian arteries in birds [ 62 ]. For this organ, only 55% of the cells were identified through flow cytometric analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The term “aortic vessels” in our paper corresponds in fact to the aortic arch and the brachiocephalic trunk. In contrast to mammals, two brachiocephalic trunks arise from the arch of the aorta and give rise to the common carotid and subclavian arteries in birds (54). This “organ” was chosen as a source of endothelial cells.…”
Section: Results – Discussionmentioning
confidence: 99%